Effect of Loading Rate and Confining Pressure on Strength and Energy Characteristics of Mudstone under Pre-Cracking Damage - Hanghang Zheng; Zhenqian Ma; Lang Zhou; Dongyue Zhang; Xuchao Liang (Energies, 2022)
In order to explore the deformation and failure law of deep surrounding rock roadway disturbed by strong dynamic pressure, the triaxial mechanical properties of mudstone samples under pre-cracking damage conditions were tested to study the deformation and failure characteristics and energy evolution mechanism in the damage process, under different loading rates and confining pressures. In the mechanical experiment, the specimen is pre-cracked to simulate the damage and failure of surrounding rock during roadway excavation, and the damage degree model of rock specimen is established. The results show that the loading rate and confining pressure have significant effects on the peak strength and energy characteristics of mudstone at the average damage degree of 0.12, and the peak strength increases with the increase in confining pressure and loading rate. Under the same confining pressure, the energy increases first, and then decreases with the increase in loading rate, and the loading rate at the turning point is called the critical loading rate. Under the same confining pressure, the closed stress of mudstone gradually increases with the increase in loading rate, and the closed stress and loading rate show a good linear relationship. Through the fitting relationship, it is found that the fitting correlation coefficient between the closed stress of mudstone and the loading rate is as high as 0.99. The elastic strain energy ratio presents a composite function of exponential function with natural constant e, which is a nonlinear process.